Fabrication of an Azithromycin Sensor - Theophile Niyitanga; Mohd Quasim Khan; Khursheed Ahmad; Rais Ahmad Khan (Biosensors, 2023)
Azithromycin (AZY) is a well-known top-prioritized antibiotic and is used by humans in strong concentrations. However, the side effects of the AZY antibiotic may cause some serious and significant damage to humans and the environment. Thus, there is a need to develop effective and sensitive sensors to monitor accurate concentrations of AZY. In the last decade, electrochemistry-based sensors have received enormous attention from the scientific community because of their high sensitivity, selectivity, cost-effectiveness, fast response, rapid detection response, simple fabrication, and working principle. It is important to mention that electrochemical sensors rely on the properties of electrode modifiers. Hence, the selection of electrode materials is of great significance when designing and developing efficient and robust electrochemical sensors. In this study, we fabricated an AZY sensor by utilizing a molybdenum disulfide/titanium aluminum carbide (MoS2@Ti3AlC2) composite as the electrode material. The MoS2@Ti3AlC2 composite was synthesized via a simple sonication process. The synthesized MoS2@Ti3AlC2 composite was characterized using a powder X-ray diffraction (XRD) method to examine the phase purity and formation of the MoS2@Ti3AlC2 composite. Scanning electron microscopy (SEM) was used to study the surface morphological features of the prepared MoS2@Ti3AlC2 composite, whereas energy dispersive X-ray spectroscopy (EDAX) was adopted to determine the elemental composition of the prepared MoS2@Ti3AlC2 composite. The glassy carbon (GC) electrode was modified with the prepared MoS2@Ti3AlC2 composite and applied as the AZY sensor. The sensing performance of the MoS2@Ti3AlC2 composite-modified GC electrode was studied using linear sweep voltammetry. The sensor demonstrated excellent performance when determining AZY and showed a good detection limit of 0.009 µM with a sensitivity of 6.77 µA/µM.cm2.